2010
DOI: 10.1007/s11205-010-9755-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of an Observational Scale of Neighborhood Characteristics

Abstract: Neighborhood, Observation, Measurement, Physical and social characteristics, Neighborhood distress, Child maltreatment, Child injury, Resident perceptions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…This is an improvement over other studies which have tended to estimate either inter-rater reliability only (Dunstan et al, 2005, Furr-Holden et al, 2010, Fuller and Muhajarine, 2010, Gauvin et al, 2005, McDonell and Waters, 2010, Weich et al, 2001 or inter-rater reliability and temporal stability separately (Millington et al, 2009, Paquet et al, 2010, Zenk et al, 2007, Pikora et al, 2002.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This is an improvement over other studies which have tended to estimate either inter-rater reliability only (Dunstan et al, 2005, Furr-Holden et al, 2010, Fuller and Muhajarine, 2010, Gauvin et al, 2005, McDonell and Waters, 2010, Weich et al, 2001 or inter-rater reliability and temporal stability separately (Millington et al, 2009, Paquet et al, 2010, Zenk et al, 2007, Pikora et al, 2002.…”
Section: Discussionmentioning
confidence: 80%
“…In cases where temporal stability or inter-rater reliability estimates have been reported, high variability across studies has been observed (Schaefer-McDaniel et al, 2009). More importantly, few tools are validated prior to being applied to large etiologic studies (Weich et al, 2001, Pikora et al, 2002, Gauvin et al, 2005, Zenk et al, 2007, Millington et al, 2009, Fuller and Muhajarine, 2010, McDonell and Waters, 2010, Paquet et al, 2010 although validation studies should be performed as formative steps to substantiate theoretical underpinnings of measurement and improve the measures themselves before being formally used in etiologic studies. As well, reliability is a necessary but insufficient component of validity: valid associations and interpretations cannot be derived from unreliable measures (Cook and Beckman, 2006).…”
Section: Limitations Of Existing Observation Toolsmentioning
confidence: 99%
“…In order to assess neighborhood disorder, researchers generally use three different approaches (McDonell & Waters, 2011;Mooney et al, 2014). One approach, based on a more objective perspective, draws from neighborhood information from governmental or commercial data sources (Cerdá et al, 2009;McDonell, 2007;Mooney et al, 2014).…”
Section: Assessing Neighborhood Disordermentioning
confidence: 99%
“…A number of limitations have been noted, however, regarding this approach, including "same source bias" (e.g., same source reporting perceived neighborhood disorder and related outcomes), confusion with other psychological constructs (e.g., fear of crime), or the influence of stereotypes and neighborhood prejudices (e.g., racial, ethnic, or socioeconomic composition) in perceptions of disorder (Caughy, O'Campo, & Patterson, 2001;Duncan & Raudenbush, 1999;Gómez, Johnson, Selva, & Sallis, 2004;Mooney et al, 2014;Sampson, 2009;, 2004Schaefer-McDaniel, Caughy, O' Campo, & Gearey, 2010). Finally, a third approach, that aims to overcome the above limitations, emphasizes the importance of using direct and systematic observations of neighborhood characteristics by trained researchers (Franzini, Caughy, Nettles, & O'Campo, 2008;McDonell, 2007;McDonell & Waters, 2011;Neil, Parke, & McDowell, 2001;Reiss, 1971;. This approach aims to obtain objective measures of neighborhood conditions, to capture a wide range of factors, which are not always available otherwise, and to allow its replication in other contexts (Caughy et al, 2001;Cohen et al, 2000;Franzini et al, 2008;McDonell & Waters, 2011;Sampson & Raudenbush, 2004;Taylor, 2001).…”
Section: Assessing Neighborhood Disordermentioning
confidence: 99%
See 1 more Smart Citation